β-Cell protection and antidiabetic activities of Crassocephalum crepidioides (Asteraceae) Benth. S. Moore extract against alloxan-induced oxidative stress via regulation of apoptosis and reactive oxygen species (ROS) - Entaz Bahar; Kazi-Marjahan Akter; Geum-Hwa Lee; Hwa-Young Lee; Harun-Or Rashid; Min-Kyung Choi; Kashi Raj Bhattarai; Mir Mohammad Monir Hossain; Joushan Ara; Kishor Mazumder; Obayed Raihan; Han-Jung Chae; et al. (BMC Complementary and Alternative Medicine, 2017)
Abstract Background Medicinal plants are becoming more popular in the treatment of various diseases because of the adverse effects of the current therapy, especially antioxidant plant components such as phenols and flavonoids have a protective role against oxidative stress-induced degenerative diseases like diabetes. Thus, the purpose of this study was to investigate β-cell protection and antidiabetic activities of Crassocephalum crepidioides (Asteraceae) Benth. S. Moore. Method The in-vitro study was conducted by the pancreatic β-cell culture and α-amylase inhibition technique which includes two methods, namely starch-iodine method and 3,5-dinitrosalicylic acid (DNSA) method. On the other hand, the in-vivo study was performed by oral glucose tolerance test (OGTT) method and alloxan-induced diabetes method by using Wistar albino rat. At the end pancreatic specimens were removed and processed for histopathological study. Result The plant extract showed significant (*p < 0.05, **p < 0.01) effect on hyperglycemia as compared to standard (Gliclazide) in OGTT. The plant extract showed efficient protection activity of pancreatic β-cell from cell death in INS-1 cell line by significantly reduced (*p < 0.05, **p < 0.01) the levels alloxan-induced apoptosis and intracellular reactive oxygen species (ROS) accumulation. In addition, the plant extract showed a significant (*p < 0.05, **p < 0.01) effect on hyperglycemia by increases in percent of β-cells present in each islet (45% – 60%) compared to the diabetic group. Conclusion The result showed that C. crepidioides had β-cell protection and antidiabetic activities in pancreatic β-cell culture and Wistar albino rat.